2017
DOI: 10.1021/acs.jpcc.7b00010
|View full text |Cite
|
Sign up to set email alerts
|

Transport Behavior of the Enantiomers of Lactic Acid through the Cyclic Peptide Nanotube: Enantiomer Discrimination

Abstract: The behavior and mechanism of the transport of the enantiomers of lactic acid (LA) in a cyclic peptide nanotube (CPNT) embedded in water, consisted of eight cyclic peptide unit ([Ala-d-Ala-L]5), have been studied in details using quantum calculations and steered molecular dynamic (SMD) simulations, separately. The SMD simulations were performed in three different phases, and it was observed that the transport behavior of two enantiomers in the CPNT is different from each other in each phase. The variation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Sánchez-Quesada et al reported that unlike cyclic octapeptide nanotubes that lack glutamate transport activity, cyclic decapeptide nanotubes can allow the transport of glutamate ions from the inside of vesicles to the extravesicular region by measuring the glutamate transport rates across vesicular membranes . It has recently been demonstrated both experimentally and computationally that CPNs can be used as a potential drug delivery system through observations of the release of 5-fluorouracil, an anticancer drug, from liposomes through a cyclic decapeptide nanotube. ,, In addition, the transport behavior of simple organic molecules including ethanol and lactic acid through CPNs was studied using molecular dynamics (MD) simulations. ,,, d -Glucose (also known as d -glucopyranose), which is one of vital hydrophilic biomolecules, plays an important role in cell metabolism…”
Section: Introductionmentioning
confidence: 99%
“…Sánchez-Quesada et al reported that unlike cyclic octapeptide nanotubes that lack glutamate transport activity, cyclic decapeptide nanotubes can allow the transport of glutamate ions from the inside of vesicles to the extravesicular region by measuring the glutamate transport rates across vesicular membranes . It has recently been demonstrated both experimentally and computationally that CPNs can be used as a potential drug delivery system through observations of the release of 5-fluorouracil, an anticancer drug, from liposomes through a cyclic decapeptide nanotube. ,, In addition, the transport behavior of simple organic molecules including ethanol and lactic acid through CPNs was studied using molecular dynamics (MD) simulations. ,,, d -Glucose (also known as d -glucopyranose), which is one of vital hydrophilic biomolecules, plays an important role in cell metabolism…”
Section: Introductionmentioning
confidence: 99%
“…The transportation of cations such as K + , Na + , Ca 2+ , and NH 4 + in CPNTs composed of varying peptides and configurations has been investigated using molecular dynamics simulations. Moreover, the movement of molecules including O 2 , CO 2 , NH 3 , , methane, methanol, , ethanol, , glucose, chloroform, ascorbic acid, lactic acid, and drugs like 5-fluorouracil , through CPNTs has been reported in the later years. Notably, many of these transport studies involved CPNTs embedded within lipid bilayers, predominantly within POPE bilayers.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of CPNs, MD simulations have been extensively utilized to examine the transport behavior of small biomolecules or organic molecules through the synthetic channel protein spanning across the lipid bilayers. For example, the permeation of biomolecules such as lactic acid and glucose through cyclic decapeptide nanotubes was scrutinized using MD simulations, which revealed that the energetic and dynamic properties of the molecules inside the CPNs depend on their isomeric composition. , …”
Section: Introductionmentioning
confidence: 99%
“…For example, the permeation of biomolecules such as lactic acid and glucose through cyclic decapeptide nanotubes was scrutinized using MD simulations, which revealed that the energetic and dynamic properties of the molecules inside the CPNs depend on their isomeric composition. 20,31 In this paper, we used all-atom MD (AAMD) simulations to examine the influence of the protonation state of glutamic acid on its transport through a cyclic decapeptide nanotube. In order to obtain the energetics and dynamic properties of the different charge states of the acid inside the CPN, the potential of mean force (PMF) and position-dependent diffusion coefficient profiles were calculated for the anionic, neutral zwitterionic, and cationic forms of glutamic acid.…”
Section: ■ Introductionmentioning
confidence: 99%